(untitled) (Itinera, 2023)
The aim of this article is to propose a hypothesis of virtual restitution of the “maritime machine” of Renaissance and Baroque theatre based on the specific case of the opening performance of the Farnese Theatre in Parma (1628). The celebrations of the wedding of Odoardo Farnese and Margherita de’ Medici culminate in the opera-tournament Mercurio e Marte, written by Claudio Achillini, set to music by Claudio Monteverdi, with scenes and machinery by Giovan Battista Aleotti and Francesco Guitti. It is a composite performance, with a strong symbolic value, conceived to celebrate the patrons and in which the main elements of the Renaissance “intermezzo” (music, dance, stage wonder) merge. The first part of the article – by Benedetta Colasanti – highlights the extent of the stage machinery, the phenomenon of technological precipitation from the construction site to the stage and the role of the state technician, tracing the story from a historical perspective and the analysis and intersection of sources (treatises, notebooks, correspondence, iconography), an operation aimed at providing the necessary data for the virtual restitution process. The second part – by Beatrice Cecchelli – describes the process of virtual restitution from a more technical point of view, illustrating the role of digital technologies and their application to the history of the performing arts.